2013
DOI: 10.1073/pnas.1309473110
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphoproteomic characterization of DNA damage response in melanoma cells following MEK/PI3K dual inhibition

Abstract: Blots were performed against DDR (p53 pSer15, histone 2AX pSer139), cell survival/ cell death (AKT pThr308, cleaved PARP), and cell signaling (ERK1/2 pThr202/Tyr204) markers and controls. Actin and GAPDH served as loading controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…1E). It was important to see if the phosphorylation sites identified to be inhibited by the compounds used in this study were also reported to be inhibited by other MEK inhibitors (29,30). Site S135/136 in neuroblast differentiation-associated protein (AHNAK) was significantly downregulated after both BRAF and MEK inhibition and has previously been shown to be regulated in response to the MEK inhibitor I (CAS 297744-42-4) in the MEK-sensitive acute myelogenous leukemia (AML) cell line, MV4-11.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1E). It was important to see if the phosphorylation sites identified to be inhibited by the compounds used in this study were also reported to be inhibited by other MEK inhibitors (29,30). Site S135/136 in neuroblast differentiation-associated protein (AHNAK) was significantly downregulated after both BRAF and MEK inhibition and has previously been shown to be regulated in response to the MEK inhibitor I (CAS 297744-42-4) in the MEK-sensitive acute myelogenous leukemia (AML) cell line, MV4-11.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, phosphorylation of S135/136 was nonresponsive to MEK inhibition in the resistant AML cell line, HEL. In a second study, melanoma cells were treated with MEKi GDC-0973 and PI3Ki GDC-0941, and immunoprecipitation of phosphopeptides was used to profile DNA damage response signaling (29). The protein SMARC4 showed initial decrease (not significant) in phosphorylation after MEKi and increased after long-term treatment with PI3Ki singularly and in combination with MEKi (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a proteomic study of cellular responses has identified DNA damage response signaling activation in response to dual inhibition of these pathways [206]. Among the most prominent responses were activation-related phosphorylation of ATM, and DNA-dependent protein kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most prominent responses were activation-related phosphorylation of ATM, and DNA-dependent protein kinases. Inhibition of these kinases in vitro enhanced cell death induced by MAPK and PI3K inhibitors [206]. …”
Section: Introductionmentioning
confidence: 99%